Applying Adult Ventilator-associated Pneumonia Bundle Evidence to the Ventilated Neonate. (June 2016) - Weber, Carla D.
Abstract : Background: Ventilator-associated pneumonia (VAP) in neonates can be reduced by implementing preventive care practices. Implementation of a group, or bundle, of evidence-based practices that improve processes of care has been shown to be cost-effective and to have better outcomes than implementation of individual single practices. Purpose: The purpose of this article is to describe a safe, effective, and efficient neonatal VAP prevention protocol developed for caregivers in the neonatal intensive care unit (NICU). Improved understanding of VAP causes, effects of care practices, and rationale for interventions can help reduce VAP risk to neonatal patients. Method: In order to improve care practices to affect VAP rates, initial and annual education occurred on improved protocol components after surveying staff practices and auditing documentation compliance. Findings/Results: In 2009, a tertiary care level III NICU in the Midwestern United States had 14 VAP cases. Lacking evidence-based VAP prevention practices for neonates, effective adult strategies were modified to meet the complex needs of the ventilated neonate. A protocol was developed over time and resulted in an annual decrease in VAP until rates were zero for 20 consecutive months from October 2012 to May 2014. Implications for Practice: This article describes a VAP prevention protocol developed to address care practices surrounding hand hygiene, intubation, feeding, suctioning, positioning, oral care, and respiratory equipment in the NICU. Implications for Research: Implementation of this VAP prevention protocol in other facilities with appropriate monitoring and tracking would provide broader support for standardization of care. Individual components of this VAP protocol could be studied to strengthen the inclusion of each; however, bundled interventions are often considered stronger when implemented as a whole.